Evaluation of a slurry ice system for the commercialization of ray (Raja clavata): Effects on spoilage mechanisms directly affecting quality loss and shelf-life - Múgica, Begoña; Barros-Velázquez, J.; Miranda, José M.; Aubourg, Santiago P. (LWT - Food Science and Technology, 2008)
8 páginas, 5 tablas, 3 figuras The application of slurry ice, a biphasic system formed by small spherical ice crystals surrounded by seawater at sub-zero temperature, was evaluated as a new storage method for ray (Raja clavata), the elasmobranch fish species that exhibits highest commercial value in the European food markets. This advanced technique was used to compare with a control batch stored 10 days in flake ice. The results obtained in the sensory analysis indicated a significant extension of the overall quality (A class fish) from 3 days (flake ice) to 6 days (slurry ice). The development of ammonia external odour was the limiting parameter in both batches and was correlated with the activity of the endogenous mechanisms involved in the degradation of proteins and non-protein-nitrogen (NPN) rather than with the activity of proteolytic microorganisms. Storage of ray in slurry ice significantly (P<0.05) slowed down both biochemical (as estimated by the follow-up of the pH, TVB-N and K-value evolution) and microbial degradation mechanisms (estimated by the development of psychrotrophes and mesophiles counts) in chilled ray muscle. According to the parameters evaluated, storage of ray in slurry ice extends the shelf-life of this elasmobranch fish species due to a better maintenance of sensory, biochemical and microbiological quality, thus facilitating its commercialization This work was supported by a project granted by the Secretarı´ a Xeral de I+D from the Xunta de Galicia (Project PGIDIT04- TAL015E) Peer reviewed